Political Legitimacy through the Narrative of Moderate Islam in Indonesia - Sainun Sainun; Amina Yusuf; Reza Fauzi Nazar; Alma Salsabilla; Dewi Putriani Yogosara Lodewijk (Mahkota Science Publishers, 2026)
This study analyses the use of moderate Islamic narratives as a strategy for political legitimisation in Indonesia. It aims to explain how political actors build legitimacy through moderate Islamic narratives and to identify the discursive strategies employed in this process. This study adopts a qualitative approach, using a critical case study design grounded in critical discourse analysis. The findings indicate that moderate Islamic narratives not only represent the values of tolerance, nationalism, and anti-extremism but can also function as political instruments to build public acceptance, strengthen the image of political actors, and manage contestations over religious identity. These narratives are ambivalent, as they can support social harmony while also potentially marginalising groups that do not conform to the dominant definition of moderation. The novelty of this study lies in its critical analysis of moderation as a discursive practice linked to legitimacy, power, and political communication. Consequently, the use of moderation narratives must be accompanied by policy commitments that are more inclusive, participatory, and sensitive to social justice, so that they do not remain mere political rhetoric.